Thin Films of Metal-Organic Framework Interfaces Obtained by Laser Evaporation - Olivia L. Rose; Anca Bonciu; Valentina Marascu; Andreea Matei; Qian Liu; Laurentiu Rusen; Valentina Dinca; Cerasela Zoica Dinu (Nanomaterials, 2021)
Properties such as large surface area, high pore volume, high chemical and thermal stability, and structural flexibility render zeolitic imidazolate frameworks (ZIFs) well-suited materials for gas separation, chemical sensors, and optical and electrical devices. For such applications, film processing is a prerequisite. Herein, matrix-assisted pulsed laser evaporation (MAPLE) was successfully used as a single-step deposition process to fabricate ZIF-8 films. By correlating laser fluency and controlling the specific transfer of lab-synthesized ZIF-8, films with user-controlled physical and chemical properties were obtained. Films’ characteristics were evaluated by scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) spectroscopy, X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, and X-ray photoelectron spectroscopy (XPS). The analysis showed that frameworks of ZIF-8 can be deposited successfully and controllably to yield polycrystalline films. The deposited films maintained the integrity of the individual ZIF-8 framework, while undergoing minor crystalline and surface chemistry changes. No significant changes in particle size were observed. Our study demonstrated control over both the MAPLE deposition conditions and the outcome, as well as the suitability of the listed deposition method to create composite architectures that could potentially be used in applications ranging from selective membranes to gas sensors.